2019
DOI: 10.1038/s41467-019-08731-y
|View full text |Cite
|
Sign up to set email alerts
|

Modified carbon nitride nanozyme as bifunctional glucose oxidase-peroxidase for metal-free bioinspired cascade photocatalysis

Abstract: Nanomaterials-based biomimetic catalysts with multiple functions are necessary to address challenges in artificial enzymes mimicking physiological processes. Here we report a metal-free nanozyme of modified graphitic carbon nitride and demonstrate its bifunctional enzyme-mimicking roles. With oxidase mimicking, hydrogen peroxide is generated from the coupled photocatalysis of glucose oxidation and dioxygen reduction under visible-light irradiation with a near 100% apparent quantum efficiency. Then, the in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
281
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 402 publications
(303 citation statements)
references
References 66 publications
10
281
0
Order By: Relevance
“…[12] For instance, we previously reported that p-C 3 N 4 with mild alkali modification exhibits high photocatalytic activity for H 2 O 2 production coupled with glucose oxidation. [13] However, how the dominant promoters of modified p-C 3 N 4 enhance the ORR kinetics in the photocatalytic process remains to be investigated. Recent studies tested the sequential arrangement of nitrogen and sulfur dopants on carbon-based catalysts (e.g., graphene or graphene-CNT) to facilitate the chemisorption of dioxygen and charge separation, which enhanced the ORR kinetics to be comparable to noble metal system.…”
Section: Introductionmentioning
confidence: 99%
“…[12] For instance, we previously reported that p-C 3 N 4 with mild alkali modification exhibits high photocatalytic activity for H 2 O 2 production coupled with glucose oxidation. [13] However, how the dominant promoters of modified p-C 3 N 4 enhance the ORR kinetics in the photocatalytic process remains to be investigated. Recent studies tested the sequential arrangement of nitrogen and sulfur dopants on carbon-based catalysts (e.g., graphene or graphene-CNT) to facilitate the chemisorption of dioxygen and charge separation, which enhanced the ORR kinetics to be comparable to noble metal system.…”
Section: Introductionmentioning
confidence: 99%
“…The atomistic-level exploration of the original active sites of nanozymes is mainly performed by simplifying the singlecomponent catalysts of noble metal nanoparticles [8][9][10], transition metal oxides [11], and carbon-based materials [12,13]. The cascade reactions catalyzed by multiple enzymes in an organism provide great impetus for preparing composite catalysts by integrating different kinds of nanozymes to mimic the complexity of biocatalysis [14,15]. Moreover, natural horse radish peroxidase is composed of a heme group and two calcium atoms, and the integrity of this complex protein is crucial for the high selectivity and efficiency of the natural homogeneous enzyme [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the second reaction of the cascade, different artificial, catalytic nanoparticles can be employed to transform H 2 O 2 into •OH, 1 O 2 (singlet oxygen), and •O − 2 (Cho et al, 2019). These catalytic nanoparticles include AuNPs (Zhang et al, 2019), iron oxide (Fan et al, 2012;Duan et al, 2015;Gao et al, 2016;Liu et al, 2018;Naha et al, 2019), silver halides (Wang et al, 2014), platinum (Liu X. et al, 2016;Wu et al, 2018), cerium oxide (Niu et al, 2007;Celardo et al, 2011), vanadium oxide (André et al, 2011), 2D metallo-porphyrinic metal-organic framework (MOF) nanosheets (Huang et al, 2017), and molybdenum FIGURE 1 | Schematics of cascade reactions for combating infectious biofilms. (A) Different substrates and enzymes involved in substrate transformations to generate different types of ROS.…”
Section: Glucose and Oxygenmentioning
confidence: 99%